KAJIAN PUSTAKA HUBUNGAN ASUPAN KOLESTEROL DAN OBESITAS SENTRAL PADA PENDERITA HIPERTENSI - Wayan Sekarini; Ni Komang Wiardani; Lely Cintari (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2022)
Hypertension has a high prevalence in Indonesia. The prevalence of hypertension and central obesity increases with lifestyle changes. This study aims to determine the relationship of cholesterol intake and central obesity in people with hypertension based on a variety of available literature. This study uses a qualitative approach with the literature review method. This research was conducted in May 2020. Data obtained from 10 journals were tabulated and analyzed. Research subjects are men and women with hypertension. Age of the sample 18 to 90 years, most women suffer from hypertension. Only 2 journals discuss the degree of hypertension. One journal states the highest degree of hypertension (25.4%) and one journal states the highest degree of state hypertension (56.6%). Of the four journals, three journals stated that their cholesterol intake was in accordance with the recommendations (300 mg per day). The type of food source of cholesterol that was most often consumed was chicken meat and chicken eggs. Three journals mention the highest sex of central obesity where women suffer the most from central obesity. Two journals state that there is a relationship between cholesterol intake and hypertension and two journals get the opposite results. Four journals say that there is a relationship between central obesity and hypertension and one journal says otherwise. Keywords: Cholesterol intake, central obesity and hypertension